2016
DOI: 10.1007/s10803-016-2740-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Robots to Therapy and Educational Objectives for Children with Autism Spectrum Disorder

Abstract: The aim of this study was to increase knowledge on therapy and educational objectives professionals work on with children with autism spectrum disorder (ASD) and to identify corresponding state of the art robots. Focus group sessions (n = 9) with ASD professionals (n = 53) from nine organisations were carried out to create an objectives overview, followed by a systematic literature study to identify state of the art robots matching these objectives. Professionals identified many ASD objectives (n = 74) in 9 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 57 publications
1
66
0
1
Order By: Relevance
“…Several robots have already been used in Robot-Assisted Therapy (RAT) with children with ASD: the NAO robot, see [13][14][15] among others; low-cost robots like AiSOY1 [16] or CHARLIE [17]; robots that use their touchscreens as part of the interaction like CARO and iRobiQ [18]; or the robot Probo which has been used for social story telling [19], to improve play skills [20], and to mediate social play skills of children with ASD with their sibling (brother or sister) [21]. See [22] for a complete survey detailing how RAT robots are mapped to therapeutic and educational objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Several robots have already been used in Robot-Assisted Therapy (RAT) with children with ASD: the NAO robot, see [13][14][15] among others; low-cost robots like AiSOY1 [16] or CHARLIE [17]; robots that use their touchscreens as part of the interaction like CARO and iRobiQ [18]; or the robot Probo which has been used for social story telling [19], to improve play skills [20], and to mediate social play skills of children with ASD with their sibling (brother or sister) [21]. See [22] for a complete survey detailing how RAT robots are mapped to therapeutic and educational objectives.…”
Section: Introductionmentioning
confidence: 99%
“…This short commentary is based on previous research [14]. Professionals (N=53) working in care organisations or special needs schools for children with ASD participated in 9 focus group sessions to provide insight into the objectives that are important for these children [14].…”
Section: Methodsmentioning
confidence: 99%
“…Technology is an accepted and efficient support tool in the therapy and education of individuals with ASD and their (informal) carers [7][8][9][10]. More, specifically, robot-assisted therapy (RAT) or robot-mediated intervention (RMI) is considered promising for children with ASD [11][12][13][14][15][16]. Although it might sound contradictory to use a robot to teach children skills in areas such as communication and social interaction, the use of robots has a number of advantages for these children.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches focus on the functions of AI on the improvement of social abilities of children with ASD. Huijnen et al (2016) have evaluated 14 identified robots in peer reviewed journals applied in studies with children with ASD, basically assessing these robots' operating mode and their functions on the social abilities of children with ASD. The aim of the research is to increase knowledge on therapy and educational objectives that professionals work on with children with ASD.…”
Section: Literature Review: Ai-assisted Intervention For Children Witmentioning
confidence: 99%